PERAN DAN KEDUDUKAN BUNDO KANDUANG DALAM NOVEL NEGERI PEREMPUAN KARYA WISRAN HADI DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INDONESIA - Dillah, Ipat; Basri, Irfani; Thamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research is purposedly done to describe the role and position of Bundo Kanduang contained in the novel Negeri Perempuan Wisran Hadi. This type of research is qualitative research with use hermeneutic method. Based on the data analysis, five roles and five forms of Bundo Kanduang position were found in Wisran Hadi's NegeriPerempuan novel, (1) the guardian of the kinship order in Minangkabau, (2) the determinant of the implementation of traditional ceremonies, (3) the form of behavior, (4) voter in deliberation, and (5) a mother. Bundo Kanduang's invisible role is the role of a wife. Furthermore, the position of Bundo Kanduang which appears in the novel, namely (1) limpapeh rumah nan gadang, (2) amban puruak pagangan kunci, (3) pusek jalo kumpulan tali, (4) sumarak dalam nagari, and (5) nan gadang basa batuah. `           Kata kunci: Bundo Kanduang, hermeneutika, kedudukan, peran